Review of recent advancements in the development and modification of gel polymer electrolytes for lithium metal batteries - Chen Lin (MATEC Web of Conferences)
The rapid evolution of mobile electronics and the global shift toward electric vehicles (EVs) have intensified the demand for high-energy- density, safe, and sustainable energy storage systems. Lithium metal batteries (LMBs), leveraging lithium metal anodes with ultrahigh theoretical capacity (3860 mAh g⁻¹), are considered promising candidates to meet these requirements. However, challenges such as lithium dendrite growth, electrolyte decomposition, and safety risks associated with conventional liquid electrolytes hinder their practical implementation. Gel polymer electrolytes (GPEs), which integrate the advantages of liquid and solid electrolytes, offer enhanced ionic conductivity, mechanical flexibility, and flame retardancy. This review systematically explores recent advancements in GPE development, focusing on the roles of plasticizers —including triethyl phosphate, cellulose acetate, succinonitrile and ionic liquids—in improving flame retardancy, ionic conductivity, and electrochemical stability. This work intends to guide the next generation in the use of plasticizers by addressing key challenges and proposing optimization strategies, leading to a rational design of GPEs for safer and more efficient LMBs. This is extremely critical and important for improving the safety, electrochemical performance, and cycling performance of gel polymer electrolytes in LMBs.